Digital Customer Experience and After-Sales Service Quality as Drivers of Customer Loyalty: A Conceptual Framework Based on Expectation Confirmation Theory. - Aisya, Disya; Erwansyah; Buana Sari, Pipit (International Conference Epicentrum of Economic Global Framework, 2025)
The rapid growth of digital technology has shifted business competition from product-oriented strategies to customer experience-oriented approaches. However, studies integrating Digital Customer Experience and After-Sales Service Quality in explaining Customer Loyalty remain limited, particularly within the industrial tools sector. This conceptual paper proposes a research framework based on Expectation Confirmation Theory (ECT) to explain the role of Customer Satisfaction as a mediating variable between Digital Customer Experience, After-Sales Service Quality, and Customer Loyalty. The framework is developed through a review of recent marketing and consumer behavior literature and proposes seven hypotheses describing the direct and indirect relationships among the constructs. The proposed model contributes to extending Expectation Confirmation Theory within digital marketing and relationship marketing literature while providing practical insights for organizations seeking to strengthen customer loyalty through enhanced digital experiences and responsive after-sales services. Future empirical studies are recommended to validate the proposed conceptual framework using Partial Least Squares Structural Equation Modeling (PLS-SEM).